Training frontline community agency staff in dialectical behaviour therapy: building capacity to meet the mental health needs of street-involved youth. Issue 2 (13th March 2017) - McCay, Elizabeth; Carter, Celina; Aiello, Andria; Quesnel, Susan; Howes, Carol; Beanlands, Heather; Langley, John; MacLaurin, Bruce; Hwang, Steven; Cooper, Linda; Lord, Christina
Abstract : Purpose: The purpose of this paper is to evaluate the effectiveness of the dialectical behavior therapy (DBT) training which was provided to community agency staff ( N =18) implementing DBT in the community with street-involved youth. Design/methodology/approach: Staff participated in a multi-component approach to training which consisted of webinars, online training, self-study manuals, and ongoing peer consultation. To evaluate assess the effectiveness of the training, questionnaires assessing evaluating DBT skills knowledge, behavioral anticipation and confidence, and DBT skills use, were completed at baseline, immediately post-training, four to six months post-training, and 12-16 months post-training. Additionally, the mental health outcomes for youth receiving the DBT intervention are reported to support the effectiveness of the training outcomes. Findings: Results demonstrate that the DBT skills, knowledge, and confidence of community agency staff improved significantly from pre to post-training and that knowledge and confidence were sustained over time. Additionally, the training was clinically effective as demonstrated by the significant improvement in mental health outcomes for street-involved youth participating in the intervention. Practical implications: Findings suggest that this evidence-based intervention can be taught to a range of staff working in community service agencies providing care to street-involved youth and that the intervention can be delivered effectively. Originality/value: These findings help to close the knowledge-practice gap between evidence-based treatment (EBT) research and practice while promoting the implementation of EBT in the community to enhance positive youth outcomes.